(untitled) (Revista de História Regional, 2007)
This article analyzes the place given to Brazil in Uruguayan history, written by Uruguays military, in a didactic book published in 1980. Members of the military in an attempt to justify the political violence the country had been put through, ventured to write history. This history is very nationalistic and consequently made them praise the conflicts throughout Uruguayan history, with Brazil. Since both dictatorships shared the same philosophy, this speech could not only stress the differences between the countries and therefore went back and forth between friend and enemy almost simultaneously. The main topics of the study are: language, Uruguays independence, the problem of boundaries and soccer. These are the points that both countries are more in contact with and at the same time have more differences.